2016
DOI: 10.1111/hae.12987
|View full text |Cite
|
Sign up to set email alerts
|

Changes in health‐related quality of life with treatment of longer‐acting clotting factors: results in the A‐LONG and B‐LONG clinical studies

Abstract: Changes in Haem-A-QoL key domains and 'Total Score' suggest that prophylaxis with long-acting rFVIIIFc or rFIXFc resulted in meaningful HRQoL improvements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
53
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(60 citation statements)
references
References 21 publications
6
53
0
1
Order By: Relevance
“…When we compare haemophilia A and B, we can see that adult patients have similar bleeding rates and HRQoL . Similar to results in our study, paediatric patients with haemophilia A that switched to BAX 855, a glycopegylated rFVIII, saw an improvement in HRQoL in all domains of the Paediatric Quality of Life Inventory.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…When we compare haemophilia A and B, we can see that adult patients have similar bleeding rates and HRQoL . Similar to results in our study, paediatric patients with haemophilia A that switched to BAX 855, a glycopegylated rFVIII, saw an improvement in HRQoL in all domains of the Paediatric Quality of Life Inventory.…”
Section: Discussionsupporting
confidence: 86%
“…patients have similar bleeding rates 9 and HRQoL. 27 Similar to results in our study, paediatric patients with haemophilia A that switched to BAX 855, a glycopegylated rFVIII, saw an improvement in HRQoL in all domains of the Paediatric Quality of Life Inventory. However, this did not reach significance in the youngest cohort.…”
Section: Hrqol Was Assessed Using the Haem-a-qol And Hrqol Respondersupporting
confidence: 88%
See 1 more Smart Citation
“…12 Clinical trial outcomes have shown for both EHL recombinant FVIII and FIX drugs that prophylaxis regimens are associated with very low annualized bleeding rates (ABRs) compared to on-demand treatment. 17,18 EHL products have been licensed at different times in the USA and Europe. 17,18 EHL products have been licensed at different times in the USA and Europe.…”
mentioning
confidence: 99%
“…37 Studies of primary prophylaxis have shown that normal or nearnormal activity with respect to joint motion and school or work attendance is achievable. Patients on prophylaxis maintain or improve physical activity levels, compared with pretreatment levels [38][39][40][41][42] and achieve similar activity levels as those with mild or moderate haemophilia. 43 Prophylaxis also enables sports participation, which in turn contributes to improved fitness, health satisfaction and psychosocial wellness.…”
Section: Comparison Between Workers With Vs Without Haemophilia Hasmentioning
confidence: 99%